GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 7153 species occurrences available in GBIF matching the query: TaxonKey: Odocoileus hemionus (Rafinesque, 1817). The dataset includes 7153 records from 66 constituent datasets: 6 records from SUI Vertebrate Collection. 42 records from ISM Mammalogy Collection. 907 records from MVZ Mammal Collection (Arctos). 211 records from KUBI Mammalogy Collection. 8 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 163 records from UAM Mammal Collection (Arctos). 5 records from CCBER Mammalogy Collection. 30 records from CRCM Vertebrate Collection. 217 records from Cowan Tetrapod Collection - Mammals. 119 records from HSU Wildlife Mammals. 74 records from Field Museum of Natural History (Zoology) Mammal Collection. 4 records from MVZ Hildebrand Collection (Arctos). 1 records from Lund Museum of Zoology (MZLU). 4 records from Naturalis Biodiversity Center (NL) - Mammalia. 114 records from Museum of Comparative Zoology, Harvard University. 6 records from NMMNH Mammal. 2155 records from iNaturalist Research-grade Observations. 2 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 64 records from University of California Museum of Paleontology. 745 records from NMNH occurrence DwC-A. 95 records from DMNS Mammal Collection (Arctos). 29 records from naturgucker. 262 records from CAS Mammalogy (MAM). 22 records from UMMZ Mammal Collection. 45 records from SBMNH Vertebrate Zoology. 50 records from LACM Vertebrate Collection. 6 records from Natural History Museum (London) Collection Specimens. 27 records from Macaulay Library Audio and Video Collection. 9 records from NatureServe Network Species Occurrence Data. 3 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 2 records from Inventario nacional de especies vegetales y animales de uso artesanal. 4 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 81 records from UWBM Mammalogy Collection. 1 records from NYSM Mammals. 22 records from Mammal specimens. 7 records from LSUMZ Mammals Collection. 14 records from Paleobiology Database. 18 records from Mammals Specimens. 11 records from FHSM Mammals Collection. 13 records from CNMA/Colección Nacional de mamíferos. 24 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 37 records from TTU Mammals Collection. 150 records from UCLA Donald R. Dickey Bird and Mammal Collection. 3 records from WNMU Mammal Collection (Arctos). 25 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 54 records from UCM Mammal Collection (Arctos). 79 records from PSM Vertebrates Collection. 90 records from UAZ Mammals. 2 records from Collection Mammalia SMF. 425 records from AMNH Mammal Collections. 11 records from UAFMC Mammals. 7 records from Geographically tagged INSDC sequences. 414 records from MSB Mammal Collection (Arctos). 5 records from MSB Host Collection (Arctos). 15 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 12 records from Animal Sound Archive. 86 records from UTEP Vertebrates. 34 records from Mammalogy Collection - Royal Ontario Museum. 2 records from Australian Museum provider for OZCAM. 2 records from macnma. 20 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 1 records from Anymals+plants - Citizen Science Data. 5 records from NCSM Mammals Collection. 1 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 39 records from UWYMV Mammal Collection (Arctos). 12 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences